Evaluating the approach run of class F11 visually impaired athletes in triple and long jumps - Theodorou, A.; Skordilis, E. (Perceptual and Motor Skills, 2012)
The present study examined stride pattern characteristics of Class F11 visually impaired long jumpers and triple jumpers. Athletes demonstrated initial ascending footfall variability followed by descending variability, on the second (long jumpers) and third (triple jumpers) stride prior to take-off, at a mean distance of 6.26 m (long jumpers) and 7.36 m (triple jumpers) from the take-off board. Toe-board-distance variability reached a maximum value of 0.36 m and 0.38 m for the long and triple jump, respectively. Last stride toe-board-distance variability was 0.29 m (long jump) and 0.25 m (triple jump). Class F11 visually impaired athletes exhibit regulation of goal-directed gait analogous to that of non-visually impaired athletes.